FOOD SECURITY OF TENANT FARMER HOUSEHOLD IN DRAWNDOWN AREA OF WONOGIRI MULTIFUNCTION DAM - Emi Widiyanti; Marcelinus Molo; Bekti Wahyu Utami (MESP–FEB UNS, 2014)
This research aimed to study the food security status of tenant farmer household in drawndown area surrounding Wonogiri multifunction dam. This study was a survey research with explanatory research taken place in five subdistricts existing surrounding Wonogiri multifunction dam with the greatest number of tenant farmer and the broadest subsiding land, including Nguntoronadi, Baturetno, Giriwoyo, Wuryantoro, and Eromoko. The data of research was collected from the result of interview with 75 tenant farmer households in five subdistricts analyzed using a descriptive analysis method. The result of research showed that (1) the food expense of farmer household was higher than non-food expense; (2) the mean energy consumption for every member of household was not even and still below Recommended Dietary Allowances (RDA) of 2000 kcal per day; (3) the mean of protein consumption per capita had surpassed the Recommended Dietary Allowances (RDA) of 50 grams per day; and (4) most farmer households were in poor food security condition.Keywords: Food security, farmer households, drawndown area.